Over-Expression and Prognostic Significance of FATP5, as a New Biomarker, in Colorectal Carcinoma - Geng, Qi-Shun; Yang, Mei-Jia; Li, Li-Feng; Shen, Zhi-Bo; Wang, Long-Hao; Zheng, Yuan-Yuan; Xue, Wen-Hua; Zhao, Jie (Frontiers in Molecular Biosciences, 2022)
Background: Fatty acid transporters (FATPs) family play an important role in the uptake and metabolism regulation of long-chain fatty acids, which influence the occurrence and developing of multiple tumors. Fatty acid transporter 5(FATP5), a member of FATPs family, participates in fatty acid transport and lipid metabolism and is related to tumor development, whose mechanism in colorectal cancer(CRC) remains unclear. Methods: In this study, we comprehensively utilized a range of relevant bioinformatic tools along with multiple databases to analyze the expression of FATPs family and investigate the biological function and prognostic value of FATP5 in colorectal carcinoma. Besides, cell proliferation and cell cycle distribution analysis, western blotting and immunohistochemistry(IHC) further validated the conclusion of bioinformatics analysis. Results: FATP5 is the only member of FATPs family which was overexpressed in colorectal carcinoma. In a survival analysis based on the GSE39582 databases, the low expression of FATP5 predicts poor prognosis in CRC. Similar results were also observed in GSE17536, GSE28814 and TCGA colon cohorts. The potential function of DNA methylation regulated the abnormal expression of FATP5 in CRC. In addition, enrichment analysis indicated that FATP5 also participates in the regulation of cell cycle. Furthermore, Gene Set Enrichment Analysis (GSEA) showed a strong negative correlation between FATP5 and cell growth, implying that it may participate in regulating cancer cell proliferation by the regulation of cell cycle G2/M transition. At last, we identified that FATP5 was overexpressed in colorectal carcinoma tissues through immunohistochemistry staining, and played an important role in cell cycle by cell proliferation and cell cycle distribution analysis. Conclusion: This study suggested that FATP5 was overexpression in colorectal carcinoma and predicted favorable prognosis, indicating it as a novel appealing prognostic marker for colorectal carcinoma.